2009
DOI: 10.1208/s12249-009-9251-0
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsions Containing Medium-Chain Glycerides as Transdermal Delivery Systems for Hydrophilic and Hydrophobic Drugs

Abstract: Abstract. We evaluated the ability of microemulsions containing medium-chain glycerides as penetration enhancers to increase the transdermal delivery of lipophilic (progesterone) and hydrophilic (adenosine) model drugs as well as the effects of an increase in surfactant blend concentration on drug transdermal delivery. Microemulsions composed of polysorbate 80, medium-chain glycerides, and propylene glycol (1:1:1, w/w/w) as surfactant blend, myvacet oil as the oily phase, and water were developed. Two microemu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 29 publications
3
42
0
5
Order By: Relevance
“…18,25 , or SLS at concentrations ranging from 0.15% to 5% (v/v) in the cell culture medium. PBS was used as the negative control at 1% concentration (v/v), while SLS was used as the positive control for all assays.…”
Section: Evaluation Of Cellular Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…18,25 , or SLS at concentrations ranging from 0.15% to 5% (v/v) in the cell culture medium. PBS was used as the negative control at 1% concentration (v/v), while SLS was used as the positive control for all assays.…”
Section: Evaluation Of Cellular Viabilitymentioning
confidence: 99%
“…43 The ability of a microemulsion to improve the transport of drugs to and across the skin is mainly affected by the composition and concentration of the microemulsion components, as well as the internal structure and type (o/w, w/o, or bicontinuous systems) of the microemulsion used. 25 Oleic acid is one of the most frequently selected oils in microemulsions, and it has been demonstrated that microemulsions containing oleic acid increased the penetration of lipophilic drugs through the skin. 44 The permeation-enhancing effect of oleic acid has been reported to be more pronounced in oil in water (o/w)-type microemulsions, and the superiority of oleic acid to increase the release of lipophilic drugs from microemulsions has been shown.…”
Section: Figurementioning
confidence: 99%
“…For retention studies, the tape stripping method [13][14][15] was performed. The skins derived after 6 h and 12 h of permeation assay were cleaned using soft paper.…”
Section: Proof Of Concept Of the Formulations By Drug Release Drug Smentioning
confidence: 99%
“…Various strategies have been employed to achieve delivery of drugs into skin. Among these strategies, microemulsions have been suggested to serve as efficient promoters of drug localization to skin [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%